The Characteristics of Sensori Quality Pressured Milkfish (Chanos chanos) with Addition of Red Ginger Extract (Zingiberofficinalevar.rubrum)duringColdTemperature Storage at 5°C - Br Hutahayan, Wika Romauli; Leksono, Tjipto; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aims to determine the effect of adding red ginger to the sensory quality of presto milkfish during cold temperature storage. The treatments were given on J0 (without red ginger), J1 (60% red ginger), J2 (70% red ginger), J3 (80% red ginger). The parameters were observed to sensory quality tests (appearance, smell, taste, and texture The addition 70% of red ginger extract was obtained the best presto milkfish (J2) with the characteristics of appearance 7.3 (neat, clean, and have a luminous golden yellow color), smell 7.5 (very fresh and fragrant smell of red ginger), taste 7.2 (very tasty, savory, soft spines), texture 7.6 (flexible texture, very dense, and compact)during storage 0 to 6 days.Keywords: Presto milkfish, Sensoritest, Red ginger extract.